ANALISIS KESALAHAN BERBAHASA INDONESIA DALAM KARANGAN TEKS EKSPOSISI SISWA SEKOLAH MENENGAH ATAS KELAS X - Azi Maulana (Universitas Maritim AMNI Semarang, 2022)
The purpose of this research is : (1) to describes the error of Indonesian language in exposition text by the students at class X, (2) causes of error, and (3) the effort which is done by the teacher and student to solve the error. This research is a qualitative descriptive research with a sample student text SMAIT Ummul Quro Bogor kelas X IPA 1 dan X IPA 3. The sampling technique used was purposive sampling. Data collection techniques used were in-depth interviews and document analysis. Data analysis technique used is the interactive analytical model that includes four components, namely data collection, data reduction, data presentation, and verification. The conclusions of this study are as follows. Firstly, the linguistic elements of language errors that often occur in the student text is divided into four errors : spelling error, diction, sentence, and paragraph. Secondly, language errors that often occur in a student text exposition caused by several factors, among others: is inadequate of language mastery, lack of examples by the teachers, the influence of foreign language, lack of writing peactice, and lack of writing time. Thirdly, the efforts have been made to minimize errors include: improving students' language mastery, having more practices in writing, implementing appropriate correction technique, and implementing a process approach to teaching writing.